2015
DOI: 10.1111/ijcs.12214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of knowledge on decision making in the context of organic cotton clothing

Abstract: This research was designed to study whether consumer knowledge on organic cotton and relevant issues influences attitude toward and price acceptance of organic cotton clothing. The effect of consumer knowledge was also studied on the way consumers use product label information in purchasing organic cotton clothing. An online survey was developed to measure the variables including experimental choice‐based conjoint models for mandatory and auxiliary label specifications. Four hundred ninety‐eight people complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 26 publications
1
49
1
1
Order By: Relevance
“…Consumer knowledge is a primary variable influencing the consumer behaviour (Brucks, 1985;Hadar et al, 2013;Oh & Abraham, 2016;Park et al, 1994). Knowledge includes three components, objective knowledge, subjective knowledge, and past experiences (Alba & Hutchinson, 1987;Brucks, 1985;Flynn & Goldsmith, 1999;Park & Lessig, 1981;Xiao, Ahn, Serido, & Shim, 2014).…”
Section: Subjective Knowledgementioning
confidence: 99%
“…Consumer knowledge is a primary variable influencing the consumer behaviour (Brucks, 1985;Hadar et al, 2013;Oh & Abraham, 2016;Park et al, 1994). Knowledge includes three components, objective knowledge, subjective knowledge, and past experiences (Alba & Hutchinson, 1987;Brucks, 1985;Flynn & Goldsmith, 1999;Park & Lessig, 1981;Xiao, Ahn, Serido, & Shim, 2014).…”
Section: Subjective Knowledgementioning
confidence: 99%
“…Based on the findings from the focus interview and the conceptual framework (i.e., the dual mediation model), the conceptual model for this study is shown in Figure 2 Consumer knowledge is defined as the extent of consumer experiences and familiarity towards a product before external search [14][15][16][17]. Past relevant studies stated that consumer knowledge is not only an primary influencer of consumer behavior but also of consumer risk perception [18][19][20]. There The dual mediation hypothesis has been used as the conceptual framework in several empirical studies.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Each of the proposed relationships is discussed below: Consumer knowledge is defined as the extent of consumer experiences and familiarity towards a product before external search [14][15][16][17]. Past relevant studies stated that consumer knowledge is not only an primary influencer of consumer behavior but also of consumer risk perception [18][19][20]. There Consumer knowledge is defined as the extent of consumer experiences and familiarity towards a product before external search [14][15][16][17].…”
Section: Conceptual Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental beliefs and values are concepts that have been widely assessed in academic research (Ellen, Wiener, & Cobb‐Walgren, ; Oh & Abraham, ; Sarabia‐Sanchez, De Juan Vigaray, & Hota, ). Many of these studies sought to understand the influence of consumers’ environmental beliefs on their probability to purchase organic or sustainable goods.…”
Section: Literature Reviewmentioning
confidence: 99%